Clinical reasoning and simulation: facilitating hypothesis prioritization using simulated patients. Data from quantitative research - Burnier, Isabelle; Ratté, Juliane; De Roock, Sophie; Benoit , Stéphanie; Denis-LeBlanc, Manon (Canadian Medical Education Journal, 2022)
Background: Prioritizing diagnostic hypotheses can be difficult for novice medical students given their limited clinical exposure. Simulated clinical reasoning (CR) clinics allow students to practice focused histories with a simulated patient (SP). The delivery of clinical data by SPs can influence hypothesis generation. Objective: This pilot study seeks to test whether the transmission of key elements through SP acting influences CR prioritization among medical students. Method: The diagnostic hypotheses of two cohorts of students of the same academic level were compared following a virtual interview with an SP. The SPs in the experimental group were given a targeted script and briefing on key elements while the SPs in the control group were given a traditional script and briefing. The difference between the distributions of frequencies of the hypotheses of the two groups was determined using the chi-square calculation. Results: The students in the experimental group prioritized expert-validated hypotheses more than those in the control group. The control group showed greater variability in their diagnostic choices. Conclusion: Targeting the delivery of key elements by SPs could be a way to help novice medical students prioritize their diagnostic hypotheses. Simulated CR clinics therefore become a space for learning about CR in the absence of clinical exposure. The risk of inducing premature closure of clinical reasoning needs further research.